2000
DOI: 10.1128/iai.68.5.2804-2807.2000
|View full text |Cite
|
Sign up to set email alerts
|

Role of Lipopolysaccharide Phase Variation in Susceptibility of Haemophilus influenzae to Bactericidal Immunoglobulin M Antibodies in Rabbit Sera

Abstract: The effect of phase variation of lipopolysaccharide (LPS) structure on the susceptibility of Haemophilus influenzae to complement-dependent killing by normal human sera and normal rat sera has been described previously. The phase-variable structure phosphorylcholine (ChoP) confers susceptibility to human serum, since ChoP on the bacterial cell surface binds to serum C-reactive protein and activates complement. In contrast, expression of gal␣1,4gal, a second phase-variable epitope that is also found on human gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Because nontypeable H. influenzae is susceptible not only to opsonophagocytic killing but also to complement-dependent bactericidal killing, if the complement source is capable of mediating both sorts of activities, it would be difficult in an assay such as this to distinguish between the two. It is well known that rabbit complement can support complement-dependent bacteriolysis of nontypeable H. influenzae and, in fact, often has naturally occurring bactericidal activity for these organisms (18). In contrast, guinea pig serum as a complement source is unable to support complement-dependent bactericidal activity with human antibodies (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because nontypeable H. influenzae is susceptible not only to opsonophagocytic killing but also to complement-dependent bactericidal killing, if the complement source is capable of mediating both sorts of activities, it would be difficult in an assay such as this to distinguish between the two. It is well known that rabbit complement can support complement-dependent bacteriolysis of nontypeable H. influenzae and, in fact, often has naturally occurring bactericidal activity for these organisms (18). In contrast, guinea pig serum as a complement source is unable to support complement-dependent bactericidal activity with human antibodies (34).…”
Section: Discussionmentioning
confidence: 99%
“…The explanation for these differences can only be speculated upon at this point. The bacterial surface of nontypeable H. influenzae is a very dynamic structure and a number of surface molecules, some of which may undergo antigenic and phase variation, are known to influence the interactions of bacteria with the host immune system (13,16,18,46,47). In the case of the HMW proteins, variation in expression level may directly influence the ability of the immune system to clear infection in vivo (5) and similar differences in levels of HMW protein expression could influence the ability of antibodies directed against these proteins to mediate opsonophagocytic activity in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Factors that undergo phase variation are commonly thought to confer some fitness advantage on the bacterial population only during a discrete phase of the infectious cycle, outside of which they may confer no benefit or even be detrimental (34,37). PCho, for example, is known to confer a number of advantages on NTHI (22,32,35,38,39) while also (in at least some structural settings) targeting bacteria for the binding of C-reactive protein or antibody and subsequent clearance (6)(7)(8)21). Consistent with this idea, Humphries and High showed that constitutive expression of the lic1 locus (and thus, presumably, expression of PCho) resulted in attenuation of encapsulated H. influenzae in an infection model of invasive disease (15).…”
Section: Discussionmentioning
confidence: 99%
“…When CRP is readily available, such as in rat or human serum during infection, ChoP-expressing H. influ-enzae strains are more sensitive to complement-mediated killing than bacteria not expressing ChoP (2,91). In contrast, ChoPexpressing bacteria have the advantage in mouse and rabbit models of bloodstream infection, in which CRP levels remain low (92,93). The pentraxin serum amyloid protein (SAP) can also bind ChoP, although no bactericidal effect has been demonstrated (94).…”
Section: Host Responses To Chopmentioning
confidence: 99%